2016
DOI: 10.1111/jomf.12327
|View full text |Cite
|
Sign up to set email alerts
|

At‐Home Father Families in the United States: Gender Ideology, Human Capital, and Unemployment

Abstract: The rising population of stay‐at‐home fathers is driven by economic conditions, human capital, and changing gender ideology. When unemployment rates increase, women become breadwinners in these families. The growing gender education gap is a crucial factor in spousal work and caregiving arrangements. The authors test these propositions by tracking individuals using data from the National Longitudinal Surveys of Youth and the Current Population Survey. They find that unemployment rates are associated with havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 45 publications
0
38
0
4
Order By: Relevance
“…To the extent that both structural and cultural changes lead to more parents in gender‐atypical work–family arrangements, these exposures may position individuals to engage in more gender‐flexible domestic behaviors. Engaging in more gender‐flexible behaviors may also lead to the adoption of more gender‐flexible attitudes (Chesley, ; Kramer & Kramer, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the extent that both structural and cultural changes lead to more parents in gender‐atypical work–family arrangements, these exposures may position individuals to engage in more gender‐flexible domestic behaviors. Engaging in more gender‐flexible behaviors may also lead to the adoption of more gender‐flexible attitudes (Chesley, ; Kramer & Kramer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Both structural and cultural factors play a role in maintaining the relationship between parenthood and gender‐traditional work and family arrangements. State policies that support male breadwinner and female caregiver families (Crompton, ; Lewis, ), a gender wage gap that favors men (Misra & Murray‐Close, ), the ability to access quality paid child care (Boeckmann et al, 2014), and the availability of cultural support for working mothers or caregiving fathers (Boeckmann et al, ; Kramer & Kramer, ) all influence parents' participation in paid work and caregiving.…”
mentioning
confidence: 99%
“…Las características de las parejas FBw dependen de la razón por la cual la pareja acoge este tipo de acuerdo. Las limitaciones económicas y del mercado laboral y las actitudes igualitarias de género son los factores principales que explican el surgimiento de las familias FBw y por qué una familia se convierte en FBw (Vitali y Arpino, 2016;Kramer y Kramer, 2016). El desempleo masculino es una razón importante que explica por qué la mujer se convierte en la principal fuente de ingresos del hogar (Vitali y Arpino, 2016;Klesment y Bavel, 2017;Schwiter y Baumgarten, 2017).…”
Section: Palabras Claveunclassified
“…El desempleo masculino es una razón importante que explica por qué la mujer se convierte en la principal fuente de ingresos del hogar (Vitali y Arpino, 2016;Klesment y Bavel, 2017;Schwiter y Baumgarten, 2017). Por otro lado, los cambios hacia actitudes de roles de género más igualitarias que se han producido en las últimas décadas han ayudado a la aceptación de este arreglo de roles (Kramer y Kramer, 2016). Las actitudes relativas a la mayor involucración de los padres en el cuidado de los hijos e hijas y de las madres con respecto al cambio de roles también son relevantes en la decisión (Fischer y Anderson, 2012;Doucet y Merla, 2007).…”
Section: Palabras Claveunclassified
“…Several researchers have also made a distinction between SAHF who are able to work and those who are not able to work because of disability or illness. Using CPS data, Kramer and Kramer () found that the effects of mother's education (i.e., human capital) on the likelihood that fathers will be SAHF was greater if fathers reported staying home to take care of children rather than reporting staying home because they were unable to work. The households of SAHF are also much more likely to be economically disadvantaged than the households of working fathers (Livingston, ).…”
Section: Trends In Fatheringmentioning
confidence: 99%